Efficacy of Health Belief Model-Based Intervention in Enhancing Breast Cancer Screening Behaviors among Women at Al-Najaf Al-Ashraf City (Medico Legal Update, 2021)
Background: Breast cancer is disease in which cells in breast tissue change and divide uncontrolled, resultingin a lump or mass. This study aims to determine the efficacy of health belief model-based intervention inenhancing women’s breast cancer screening behaviors.Method: A randomized controlled trial was conducted using the Health Belief Model. The study includeda systematic random sample of 110 women. Women who age 22-68-years were selected from Banks in AlNajaf Al-Ashraf City.Data were collected through a self-report instrument that includes women’s sociodemographic characteristicsof age, marital status, and economic status, the Perceived Susceptibility Scale, the Perceived Benefits Scale,the Self-Efficacy Scale, the Health Motivation, the Perceived Severity Scale, and the Perceived BarriersScale. Data were analyzedusing the statistical package forsocial sciences, version 26.The study results revealed that HBM-based intervention was efficacious in enhancing the PerceivedSusceptibility, the Perceived Benefits, the Self-Efficacy, the Health Motivation, the Perceived Severity,and the Perceived Barriers for women in the study group. The researcher concluded that the HBM-basedintervention we as efficacious in enhancing women’s screening behaviors for breast cancer.Conclusion: The researcher concluded that the HBM-based intervention was effective in enhancing women’sbreast cancer screening behaviors.